COVID-19 detection: Comparison and accuracy of several diagnostic tests - Mati Ullah; Muhammad Ibrar; Salah Uddin Khan; Habib Ullah; Nasir Ali Khan (Novel Research in Microbiology Journal)
The emergence of coronavirus disease 2019 (COVID-19) pandemic caused by the severe acute respiratory syndrome coronavirus (SARS-CoV-2) has created a global alarming situation. Initially, diagnosis of the virus was conducted by a combination of different assays including; electron microscopy (EM), computed tomography (CT) scan and whole-genome sequencing. However, such time-consuming diagnosis has critically highlighted the need for a fast and specific testing approach for earlier detection. It is expected that the ongoing research advances and the continuing efforts for the fight against COVID-19 will soon bring a fruitful discovery in in vitro diagnostics techniques. Meanwhile, the efficiency and performance of any novel diagnostic approach should be censoriously analyzed before it comes into practice. The aims of this study were to evaluate and compare the different diagnostic tests recommended by the World Health Organization (WHO) for earlier detection of the novel SARSCoV-2. We found that the Clustered regularly interspaced short palindromic sequence (CRISPR/Cas) detection has relatively higher efficiency, compared to all the other tests. Therefore from this report, we concluded that the discovery of CRISPR/Cas based in vitro diagnostics will minimize the time limit as well as the cost for COVID19 detection.